Windows Server 2019 Inside Out - Thomas, Orin (Microsoft Press, 2020)
Conquer Windows Server 2019-from the inside out! Dive into Windows Server 2019-and really put your Windows Serverexpertise to work. Focusing on Windows Server 2019's most powerful and innovative features, this supremely organized reference packs hundreds of timesaving solutions, tips, and workarounds-all you need to plan, implement, or manage Windows Server in enterprise, data center, cloud, and hybrid environments. Fully reflecting new innovations for security, hybrid cloud environments, and Hyper-Converged Infrastructure (HCI), it covers everything from cluster sets to Windows Subsystem for Linux. You'll discover how experts tackle today's essential tasks-and challenge yourself to new levels of mastery." Optimize the full Windows Server 2019 lifecycle, from planning and configuration through rollout and administration " Leverage new configuration options including App Compatibility Features on Demand (FOD) or Desktop Experience " Ensure fast, reliable upgrades and migrations " Manage Windows servers, clients, and services through Windows Admin Center " Seamlessly deliver and administer core DNS, DHCP, fi le, print, storage, and Internet services " Use the Storage Migration Service to simplify storage moves and configuration at the destination " Seamlessly integrate Azure IaaS and hybrid services with Windows Server 2019 " Improve agility with advanced container technologies, including container networking and integration into Kubernetes orchestration clusters " Deliver Active Directory identity, certifi cate, federation, and rights management services " Protect servers, clients, VMs, assets, and users with advanced Windows Server 2019 security features, from Just Enough Administration to shielded VMs and guarded virtualization fabrics " Monitor performance, manage event logs, confi gure advanced auditing, and perform backup/recovery Windows Server 2019 For Experienced Windows Server Users and IT Professionals " Your role: Experienced intermediate to-advanced level Windows Server user or IT professional " Prerequisites: Basic understanding of Windows Server procedures, techniques, and navigation